2013
DOI: 10.1016/j.neurobiolaging.2012.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Healthy aging is associated with increased neural processing of positive valence but attenuated processing of emotional arousal: an fMRI study

Abstract: Arousal and valence play key roles in emotional perception, with normal aging leading to changes in the neural substrates supporting valence processing. The objective of this study was to investigate normal age-related changes in the neural substrates of emotional arousal processing. Twenty-three young and 23 older, healthy women underwent functional magnetic resonance imaging as they viewed images which were neutral or positive in valence and which varied in arousal level from low to high. Using a parametric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 81 publications
(100 reference statements)
4
36
1
1
Order By: Relevance
“…This metaanalytic network of regions has been implicated in basic visual processing, participating in visual memory (Todd, Won Han, Harrison, & Marois, 2011), as well as recognition and naming of words (Price et al, 1994; Bookheimer, Zeffiro, Blaxton, Gaillard, & Theodore, 1995; Mechelli, Humphreys, Mayall, Olson, & Price, 2000). The involvement of the visual perception network in emotion is well documented (Keightley et al, 2003; Kehoe, Toomey, Balsters, & Bokde, 2013; Isenberg et al, 1999), and has been discussed in several meta-analyses (Kober et al, 2008; Fusar-Poli et al, 2009; Vytal & Hamann 2010). Furthermore, neuroimaging evidence has suggested that activation in the visual cortices may be modulated by affective stimuli (Vuilleumier & Pourtois, 2007; Stolarova, Keil, & Moratti, 2006) or by differential eye fixation strategies when perceiving affect-laden stimuli (van Reekum et al, 2007).…”
Section: | Discussionmentioning
confidence: 99%
“…This metaanalytic network of regions has been implicated in basic visual processing, participating in visual memory (Todd, Won Han, Harrison, & Marois, 2011), as well as recognition and naming of words (Price et al, 1994; Bookheimer, Zeffiro, Blaxton, Gaillard, & Theodore, 1995; Mechelli, Humphreys, Mayall, Olson, & Price, 2000). The involvement of the visual perception network in emotion is well documented (Keightley et al, 2003; Kehoe, Toomey, Balsters, & Bokde, 2013; Isenberg et al, 1999), and has been discussed in several meta-analyses (Kober et al, 2008; Fusar-Poli et al, 2009; Vytal & Hamann 2010). Furthermore, neuroimaging evidence has suggested that activation in the visual cortices may be modulated by affective stimuli (Vuilleumier & Pourtois, 2007; Stolarova, Keil, & Moratti, 2006) or by differential eye fixation strategies when perceiving affect-laden stimuli (van Reekum et al, 2007).…”
Section: | Discussionmentioning
confidence: 99%
“…Furthermore, it is relatively more responsive to positive than negative stimuli in older adults compared with younger adults (Erk et al, 2008, Ge et al, 2014, Kehoe et al, 2013, Leclerc and Kensinger, 2011, Mather et al, 2004, Waldinger et al, 2011, but see Moriguchi et al, 2011 for no age-by-valence effects in amygdala). Thus, the amygdala does not stop responding to emotional stimuli in later life, but instead, shifts which valence it is most responsive to.…”
Section: Relations Between Emotional Processing In Aging and Brain Fumentioning
confidence: 99%
“…In particular, a study by Kehoe and colleagues [57] found that older adults showed greater activation in the left amygdala, left middle temporal gyrus and right lingual gyrus in response to positive valence while, on the contrary, they showed reduced reactivity to emotional arousal, in occipital and temporal visual cortices, the left inferior parietal cortex and in bilateral supplementary motor areas.…”
Section: Introductionmentioning
confidence: 99%